Long shelf life tomato hybrids with improved fruit color intensity - Cá, José António; Maluf, Wilson Roberto; Gomes, Luiz Antonio Augusto; do Nascimento, Ildon Rodrigues; Faria, Marcos Ventura; Licursi, Vicente; Moretto, Paulo (Pesquisa Agropecuaria Brasileira, 2006)
The objective of this work was to evaluate the feasibility of simultaneous use of the ripening mutant (norA or rin) and color enhancing mutant genes (ogc and/or hp) in tomato hybrids with different genotypic backgrounds and genotype combinations. The trial was set up in a plastic house, with in RCB design with 20 genotypes and 3 replications. Ripening mutant genotypes nor+/norA and rin+/rin reduced early yields, but not total yields. Genotypes bearing one or more mutants norA, rin, ogc or hp showed improved shelf life in comparison to that of normal genotypes. The constitution rin+/rin showed the poorest internal color among the genotypes tested. There was a positive effect of ogc+/ogc, ogc/ogc and/or hp+/hp on the internal fruit color of normal nor+/norA and rin+/rin genotypes, but the effect in rin+/rin genotypes was not enough as to insure a final color similar to that of normal genotypes. Genotypic constitutions ogc+/ogc and ogc/ogc, in the ogc locus, showed similar positive effects on both internal color and color of placentary jelly. The genotypic constitutions nor+/norA ogc+/ogc or nor+/norA ogc+/ogc hp+/hp were deemed the most promising genotypic combinations to attain improvements in both fruit shelf life and internal color.